2.4GHZ ISM band congestion : WLAN and WPAN performance analysis - Mahalin, Nur Hija (2009)
The 2.40 GHz frequency band is also known as the ISM (Industrial Scientific and Medical) band, is a license free band allocated for a variety of consumer applications: environmental monitoring, agriculture, medical care, smart buildings, factory monitoring and automation, and numerous military applications. A wireless sensor network (WSN) consist of small nodes with sensing, computation, and wireless communications capabilities, is an exciting new technology and can also be considered as the underlying infrastructure that will be an integral part of future ubiquitous and embedded computing applications. Due to the independent design and development in WSN, together with the unexpected dynamics during deployment of co-eXisting networks and devices, within the same frequency spectrum, IT is crucial to ensure that each wireless technology maintains and provide its desired performance requirements. This paper proposes to study multifrequency functionality among overlapping but cooperative WSNs and potential interferences with Wireless Local Area Network (WLAN) are examined according to the impact on the throughput performance of WLAN and WPAN devices when coexisting within a certain environment.